Controlling Listeria monocytogenes in ready-to-eat leafy greens by amphipathic α-helix peptide zp80 and its antimicrobial mechanisms. (December 2021) - Yi, Lanhua; Zeng, Ping; Wong, Kwok-Yin; Chan, Kin-Fai; Chen, Sheng
Abstract: Pathogens can stick to the surfaces of leaves and ready-to-eat leafy greens are usually eaten without any lethal treatment to remove them. In this study, the peptide zp80 was chemically synthesized and purified. It had α-helix structure by circular dichroism spectroscopy analysis. zp80 reduced aerobic bacteria in ready-to-eat vegetable salad and lettuce. zp80 had MIC values of 2–8 μM against 7 foodborne pathogens, it was 2 μM to Listeria monocytogenes . Growth curve and time-kill curve showed that zp80 exhibited bactericidal mode with partial cell lysis. Confocal microscope indicated that zp80 was able to penetrate inside the cell membrane and distributed in cytoplasm and nucleus. Cell deformation with sunken surface was observed using scanning electron microscope. Further, results of SYTOX green and DiSC3 (5) showed that zp80 had membrane depolarization caused by pore formation. After entering cytoplasm of L. monocytogenes, zp80 could bind to DNA, and then precipitated DNA. In addition, zp80 induced the production of intracellular reactive oxygen species (ROS), which played a key role on lethal effect by analysis using SYTO9 and PI. Hurdling treatment with 64 μM zp80 reduced 4.18 log units of L. monocytogenes in fresh-cut lettuce and alleviated browning after 7-day storage. Highlights: ● zp80 had a MIC value of 2 μM to L. monocytogenes. ● zp80 reduced aerobic bacteria in ready-to-eat lettuce with better effect than nisin. ● zp80 had membrane depolarization caused by pore formation. ● zp80 bound to DNA and caused DNA precipitation. ● zp80 induced the production of intracellular ROS.